2020
DOI: 10.3390/nu12071933
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypoxic Exposure with High Dose of Arginine Impact on Circulating Mediators of Tissue Regeneration

Abstract: Intermittent exposure to hypoxia (IHE) increases production of reactive oxygen and nitrogen species which, as signalling molecules, participate in tissue injury–repair–regeneration cascade. The process is also stimulated by arginine whose bioavailability is a limiting factor for NO synthesis. The effects of IHE in combination with arginine (Arg) intake on myogenesis and angiogenesis mediators were examined in a randomized and placebo-controlled trial. Blood samples were collected from 38 elite athletes on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
1
2
0
2
Order By: Relevance
“…Using correlation analysis, Sonnweber et al (2014) found that PDGF is associated with hypoxia mediated hepcidin repression in humans. Interestingly, Zembroń-Łacny et al (2020) recently showed that PDGF remained significantly higher 1 day after the passive 12-day intermittent hypoxic exposure, suggesting that PDGF could potentially have contributed to maintaining the downregulation of hepcidin observed in our study. However, we did not measure PDFG’s response to the LH-TL protocol–this is worth considering for future research.…”
Section: Discussionsupporting
confidence: 59%
“…Using correlation analysis, Sonnweber et al (2014) found that PDGF is associated with hypoxia mediated hepcidin repression in humans. Interestingly, Zembroń-Łacny et al (2020) recently showed that PDGF remained significantly higher 1 day after the passive 12-day intermittent hypoxic exposure, suggesting that PDGF could potentially have contributed to maintaining the downregulation of hepcidin observed in our study. However, we did not measure PDFG’s response to the LH-TL protocol–this is worth considering for future research.…”
Section: Discussionsupporting
confidence: 59%
“…On the one hand, in combination with growth factors, they participate in muscle regeneration and repair. On the other hand, however, the local persistence of RONS sustained by infiltrated neutrophils may cause further injury by oxidatively damaging differentiating myoblasts and myotubes thus delaying the complete restoration to health [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…If the homogeneity and normality assumptions were violated, the Kruskal-Wallis non-parametric test was used. Additionally, eta-squared (η 2 ) was used as a measure of effect size, which is indicated as having no effect if 0 ≤ η 2 < 0.05, a small effect if 0.05 ≤ η 2 < 0.26, a moderate effect if 0.026 ≤ η 2 <0.64 and a large effect if η 2 ≥ 0.64 according to our previous study [20]. The ideal sample size for a 30-person group was n = 28, whereas for a 20-person it was set at n = 20 to demonstrate significant differences (confidence level 95% and margin error 5%).…”
Section: Discussionmentioning
confidence: 99%